Stone sawing machine at the Temple of Artemis in Jerash, Jordan - Genaro González; Blas Herrera (Dyna, 2023)
Finishing materials play an important role in architectural design. Since ancient times, claddings made of noble materials (mainly stone) convey grandeur. Clearly, there was a technology to transform quarry stones into slabs using stone sawing machines. An example of this comes from the excavation work carried out in 1930 at the Temple of Artemis in Jerash (6th century AD). The archaeologists found a facility which was classified as a stone sawmill. The efficiency of such machines, their construction method and their resistance characteristics have not been studied as yet. This paper aims to define such parameters for the stone sawing machine located in Jerash.